SPANISH GIVEN NAMES AND SURNAMES IN CERTIFIED TRANSLATION INTO POLISH - NOWAKOWSKA-GŁUSZAK, Anna (Comparative Legilinguistics, 2016)
The purpose of this paper is the issue of the transposition of Spanish given names and surnames in certified translations into Polish. Answering the question how the translator should treat proper names in the documents translated, the author is trying to collect and systematize the principles of inflection of Spanish given names and surnames in their translations into Polish. In order to attain this, on the basis of the statistical data provided by Instituto Nacional de Estadísticas, she carries out the morphological analysis of one hundred most popular female and male given names and surnames, and groups them according to their inflection, in order to determine the patterns and principles of their inflection in Polish. Apart from the linguistic issues, the author also raises legal issues, making a survey of the most significant legal acts regulating the principles of naming and registering given names and surnames in Spain, as well as the principles of “translating” proper names in certified translations into Polish. The multifaceted analysis of the issue enables the author to conclude that the inflection of Spanish given names and surnames in Polish is extremely complex and confirms the necessity to educate translators of specialized texts also in the scope of their native tongue.